Perceptions of affiliates to private pension funds (2018)
The following paper studies the determinants of choosing a private pension fund institution by processing a questionnaire of 514 affiliates. The questionnaire attempts to measure perceptions of the consumer with respect to their private pension fund institution. Using a structural equation model, we found that socioeconomic variables are irrelevant but some perceptions like the return of portfolio and leadership of the private pension fund were relevant in the choice of a private pension fund institution. We contrast the model in two different periods of time between 2009 and 2016. The periods before and after financial turmoil in the stock market.